The challenge of development for the third world issues and outlooks - Morata, Josefa Rizalina A. (1976)
A review of Alan Richard Kasdan, The Third World: A New Focus For Development (Cambridge: Schenkman Publishing Co., 1973), 121 pp.; and Robert S. McNamara, One Hundred Countries, Two Billion People: The Dimensions of Development (New York: Praeger Publisher, 1973), 139 pp.
Keywords: Books -- Reviews; Developing countries; Public administration